Neutrophil Depletion Changes the N-Glycosylation Pattern of IgG in Experimental Murine Sepsis - Yaykasli, Kürsat Oguz; van Schie, Karin A.; Toes, René E.M.; Wuhrer, Manfred; Koeleman, Carolien A.M.; Bila, Galyna; Negrych, Nazar; Schett, Georg; Knopf, Jasmin; Herrmann, Martin; Bilyy, Rostyslav (International Journal of Molecular Sciences, 2024)
Sepsis is a life-threatening condition with a rising disease burden worldwide. It is a multifactorial disease and is defined as a dysregulated host response to infection. Neutrophils have been shown to be involved in the pathogenesis of sepsis by exacerbating inflammation. However, the exact effector mechanism of action still remains a mystery. Changes in the glycosylation pattern of the immunoglobulin G (IgG) Fc region are described for several diseases including meningococcal sepsis. In this study, we investigated the possible contribution of neutrophils and neutrophil implication, potentially related to degranulation or neutrophil extracellular trap (NET) formation in changing the IgG Fc N-glycosylation pattern in a murine sepsis model. We have measured the serum level of cytokines/chemokines and immunoglobulins, the serum activity of neutrophil elastase (NE), and analyzed the IgG Fc glycosylation pattern by Liquid Chromatography-Electrospray Ionization-Mass Spectrometry (LC-ESI-MS) and Lectin enzyme-linked immunosorbent assay (ELISA). We observed an increased activity of NE- and neutrophil-associated cytokines such as keratinocyte chemoattractant (KC) with the development of sepsis. Regarding the IgG Fc N-glycosylation, we observed an increase in fucosylation and α1,3-galactosylation and a decrease for sialyation. Interestingly, these changes were not uniform for all IgG subclasses. After depletion of neutrophils, we saw a change in the exposure of fucose and α2,6-linked sialic acid during the time course of our experimental sepsis model. In conclusion, neutrophils can influence changes in the IgG glycosylation pattern in experimental sepsis.
CRIS-Team Scopus Importer:2024-07-12
Keywords: IgG Fc glycosylation; neutrophil extracellular traps (NETs); neutrophils; sepsis